Initial model based Malaysia regulations broadband technology over power line networks - Sheik Osman, Wan Rozaini; Nizar, Kashif; Altrad, Abdallah Mahmoud Mousa (2012)
Broadband over Power lines (BPL) is a technology that works by transmitting high frequency signals through the same power cable used for carrying electricity to households for high speed transmission of data.Currently, there are trials on BPL and commercial deployments underway and completed in several countries such as Europe countries, Australia and Korea.Even though, broadband technology is no longer considered as a new technological invention.But, the broadband adoption rate in Malaysia is still below expectation level as compared to many countries. Furthermore, there is lack of study that explores the BPL technology in Malaysia.Therefore, this paper is built an initial BPL network system model based on Malaysia BPL regulations and related researches in order to construct affordable communication technology that can increase household internet access penetration rate up to 75% as recommended in Malaysia National Broadband Initiative 2010.